SUPERVISI MANAJERIAL BERBASIS DELPHI METHOD DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH PESANTREN - A. Faizin; Ahmad Thohirin; Mumayyizah (Akademika, 2025)
Managerial supervision is not just an administrative task, but a key strategy in building a quality education system. In the current era of educational transformation, school principals through managerial supervision play an important role in managing and supervising the learning process so that it runs effectively and with quality. This study aims to find out several things in Al Ishlah Junior High School, including the implementation of head managerial supervision, describing the Delphi method applied in the managerial supervision process and managerial supervision based on the Delphi method can improve the quality of learning. This research uses a qualitative research method, where the researcher must make complex images, test words, present the respondents' opinions in detail, and conduct real-life case studies. Qualitative research is research that aims to understand a phenomenon experienced by the subject, such as behavior, perception and problems related to the subject. This study uses a qualitative approach with a case study type to explore the implementation of Delphi Method-based managerial supervision in improving the quality of learning. The result of this study is that managerial supervision at Al Ishlah Bungah Gresik Junior High School is carried out with a measurable and sustainable plan by the principal through monitoring teacher development activities and strengthening school management. The Delphi method approach is used through structured discussions and the collection of opinions from teachers, staff, and school committees in several stages that are used to formulate a vision and mission, setting priority programs collaboratively. Managerial supervision based on the Delphi method is able to improve the quality of learning because it encourages teacher involvement in producing more appropriate decisions so as to increase teacher motivation, and the achievement of student learning outcomes.